IPHSJ 2020
DOI: 10.36648/1791-809x.14.1.692
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nurses Job Satisfaction and Organizational Commitment

Abstract: Nurses satisfaction has been linked to and impacted on many issues in the health care system, such as the outcome of care, patient satisfaction and organizational commitment. Organizational commitment and job satisfaction are attitudes related to jobs that have received considerable attention from researchers worldwide. Nurse role considered as very important to provide health care for patient with respect the improving the quality of care in health institutions.This study aimed: To assess the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 6 publications
1
20
1
Order By: Relevance
“…Nevertheless, several investigations have found that job satisfaction is strongly related to nurse attitudes towards patient safety culture and quality of care (Asif et al, 2019;Wang, Chou et al, 2019). Moreover, past studies have highlighted the importance of increasing job satisfaction among nurses to strengthen their commitment to their organisation and patients (Hakami et al, 2020). In one study, high job satisfaction and commitment were attributed to a strong sense of purpose and meaning among nurses.…”
Section: Job Satisfaction and Engagement Affect Nurse Caring Behavioursmentioning
confidence: 99%
“…Nevertheless, several investigations have found that job satisfaction is strongly related to nurse attitudes towards patient safety culture and quality of care (Asif et al, 2019;Wang, Chou et al, 2019). Moreover, past studies have highlighted the importance of increasing job satisfaction among nurses to strengthen their commitment to their organisation and patients (Hakami et al, 2020). In one study, high job satisfaction and commitment were attributed to a strong sense of purpose and meaning among nurses.…”
Section: Job Satisfaction and Engagement Affect Nurse Caring Behavioursmentioning
confidence: 99%
“…In particular, nurses' job satisfaction indicates the extent to which nurses are satisfied with their workplace, nature of work or leaders among others. 6 Nurses who are contented with the job are highly committed and devoted to their professional calling thus enhancing their productivity and quality of patient care. 6,7 Nurses' job satisfaction has been shown to be influenced by a constellation of factors including organizational commitment, 6 turnover intention 8 and burnout.…”
Section: Original Articlementioning
confidence: 99%
“…6 Nurses who are contented with the job are highly committed and devoted to their professional calling thus enhancing their productivity and quality of patient care. 6,7 Nurses' job satisfaction has been shown to be influenced by a constellation of factors including organizational commitment, 6 turnover intention 8 and burnout. 9 One of the key factors influencing nurses' job satisfaction is chief nurse's ward management behavior.…”
Section: Original Articlementioning
confidence: 99%
“…Nursing profession is a vital pillar of society, and healthcare delivery relies heavily on nursing staff (20) . Challenges among nurses internationally are several such as suffering from absenteeism, high turnover rate with low organizational commitment (18) . So it is imperative to find path way for enhancement the nurses' (2) .More specifically, teams are said to contribute to better outcomes for organizations due to enhance performance, productivity and commitment to the organization (14) .…”
Section: Significance Of Studymentioning
confidence: 99%
“…Similar to this, personal characteristics, roles and job characteristics, structural characteristics, work experience, and status of the working environment are expressed as factors affecting the degree of organizational commitment (14) . (18,19)…”
Section: Introductionmentioning
confidence: 99%